2019
DOI: 10.1002/adfm.201807604
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally Treated SnO2 as the Electron Transport Layer in High‐Efficiency Flexible Perovskite Solar Cells with a Certificated Efficiency of 17.3%

Abstract: Perovskite solar cells (PSCs) are one of the most promising solar energy conversion technologies owing to their rapidly developing power conversion efficiency (PCE). Low-temperature solution processing of the perovskite layer enables the fabrication of flexible devices. However, their application has been greatly hindered due to the lack of strategies to fabricate high-quality electron transport layers (ETLs) at the low temperatures (≈100 °C) that most flexible plastic substrates can withstand, leading to poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 53 publications
0
53
0
Order By: Relevance
“…Recently, it was reported that adding cesium (Cs) at the cation site can significantly reduce fabrication temperature for perovskite films . Due to the abundance of the precursor components and ease of fabrication, a variety of low‐temperature techniques has been developed to promote the performance of the PSCs in the past few years.…”
Section: Perovskite Absorber Layersmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it was reported that adding cesium (Cs) at the cation site can significantly reduce fabrication temperature for perovskite films . Due to the abundance of the precursor components and ease of fabrication, a variety of low‐temperature techniques has been developed to promote the performance of the PSCs in the past few years.…”
Section: Perovskite Absorber Layersmentioning
confidence: 99%
“…The resulted FPSCs exhibited a PCE of 18.1% and maintained 85% of the initial PCEs after 1000 bending cycles. In addition, the device held impressive stability that maintained over 90% of the initial PCE after a 30‐day storage in ambient air with no encapsulation . Fan and coworkers prepared SnO 2 ETLs with a room‐temperature sputtering process .…”
Section: Carrier Transport Layersmentioning
confidence: 99%
See 3 more Smart Citations